Adverse events related to medication administration in a Taquari Valley hospital - Kellen Cristina Januário Benedetti Alves; Paula Michele Lohmann; Arlete Eli Kunz da Costa; Fernanda dos Santos (Universidade de Santa Cruz do Sul, 2020)
Background and Objectives: The medication process in the hospital environment is one of the most important activities to ensure efficacy in the patient's therapy. The objective of this study was to know the perception of the nursing team about the occurrence of adverse events related to drug administration in a hospital in Vale do Taquari, Rio Grande do Sul. Methods: This is a descriptive exploratory study with a qualitative approach-quantitative. Data were collected through the application of a questionnaire to nursing professionals, constituting a sample of fifty-eight interviewees. The analysis was made through descriptive statistics. Results: Of the participants, 96.6% knew the steps to avoid medication errors, and 79.3% had already made some mistake in their professional practices in the institution. The most frequent error was the erroneous administration dose of 43.5%, with 97.3% of the professionals already perceived some error in the medication process and 30% considered the work overload to be an aggravating factor for the occurrence of errors. Regarding the professional's behavior regarding the error, 80.4% communicated verbally to the supervising professional and as a consequence received verbal guidance 78.3% of the time. As for feelings about the error 36.8% revealed to feel fear of harming the patient. Conclusion: These findings point to serious potential errors that impair patient safety; however, it is noted that verbal guidelines are offered avoiding punishment, but the incentive for reporting the error is precarious, making it difficult for the team to identify potential errors and implement barriers to avoid them.